The Relationship Between Husband's Support and Complete Neonatal Visits in Sumberbaru Community Health Centre Working Area - Laras Yulinar Paulinawati Kamagi; Syiska Atik Maryanti; Hendro Prasetyo (Universitas Bondowoso, 2023)
ABSTRACT Background: Neonates are the first period of life outside the womb until the age of 28 days, when there is a very big change from life inside the womb to outside the womb. More than half of the world's infant deaths occur in the first year of life, especially in the neonatal period. The neonatal period is the most vulnerable period for babies to face the risk of health problems. Method: Analytical research design, cross-sectional research approach with a population of all mothers who have babies aged 1-3 months with a total of 190 respondents. The sample technique used is simple random sampling. Data was collected using a questionnaire and the Kesehatan Ibu dan Anak handbook. Data analysis used the Chi Square statistical test. Results: This study showed that the majority (57.3%) of mothers received high support from their husbands in making or receiving neonatal visits and the majority (60.5%) of mothers made complete neonatal visits. Value analysis with a p-value of 0.000 <α 0.05. Conclusion: There is a relationship between husband's support and complete neonatal visits in the working area of the Sumberbaru Health Center. Therefore the husband must provide adequate support to the mother so that the mother can be motivated to make and receive a complete neonatal visit.